Everyday experiences of people living with MCI or dementia: a scoping review. (20th December 2022) - Huizenga, Jacoba; Scheffelaar, Aukelien; Bleijenberg, Nienke; Wilken, Jean Pierre; Fruijtier, Agnetha D.; Van Regenmortel, Martine R.F.
Abstract: Background: Increasing attention has been paid to the 'voice' of people living with MCI or dementia, but there is a lack of clarity about how everyday life is exercised, lived, and understood from this insider's perspective. The current study aimed to explore and identify the everyday life experiences, challenges and facilitators, of home living individuals with MCI and dementia. Method: Our study adopted a scoping review methodology, guided by the Joanna Briggs Institute Reviewers Manual. Eight databases were searched, resulting in 6345 records, of which 58 papers were included in the review. Only qualitative studies were included, published between 2011 and 2021. Analysis was done by descriptive content analysis. Result: Included study characteristics are summarized in Table 1. Our findings were categorized into seven spheres of everyday life: experiences related to the condition, the self, relationships, activities, environment, health and social care, and public opinions [Figure 1, Table 2]. Results show the many disruptions and losses in everyday life and the ways people try to adapt to these changes. Highlighted in every area is the importance of reciprocal relationships and being engaged as citizens in the community in a meaningful way. Included studies showed no differences between groups in the impact on the experience of everyday life, such as between MCI and dementia. Conclusion: This review shows that the change of focus from healthcare to all aspects of everyday life provides insight into the insider's perspective of people living with dementia. The majority of included studies emphasize the social needs of people living with MCI or dementia. All areas of everyday life seem to be closely intertwined and reflect an socioecological model [1], [2], [3]. Furthermore, perhaps one of the defining aspects of MCI according to the current definition, that symptoms do not interfere with daily life, requires more nuance. More research is needed on factors that promote and impede the sense of reciprocity and belonging, as experienced by people living with MCI and dementia.